PENGARUH PENGENDALIAN INTERNAL DAN KEPUASAN KERJA TERHADAP KECENDERUNGAN KECURANGAN (FRAUD) (Studi pada Mc Donald’s Cabang Malang) - ahmad anas athoulloh (Jurnal Akuntansi Indonesia, 2019)
This research aims to determine the effect of internal control and job satisfaction on the tendency of fraud in Mc Donald's Malang branch. The population in this research all employees of Mc Donald's Malang branch, amounting to 3 branches. The questionnaire was distributed to 49 respondents with the determination of the selected sample using the purposive sampling method. he data in this research were analyzed by using multiple linear regression analysis techniques. The results of this research stated that partially internal control does not affect the tendency of fraud, while job satisfaction has a negative and significant effect on the tendency of fraud. Simultaneously internal control and job satisfaction influence the tendency of fraud.